EFEKTIVITAS PENGGUNAAN GEMINI DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN DASAR – DASAR MANAJEMEN PERKANTORAN DAN LAYANAN BISNIS - Nabilla Salsa Edindha Putri; Febrika Yogie Hermanto; Fitriana Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effectiveness of using Gemini as a learning medium in improving student learning outcomes in the subject of Fundamentals of Office Management and Business Services in class X MPLB SMKS PGRI 2 Sidoarjo. The research method used was an experiment with a quasi-experimental Nonequivalent Control Group Design. The sample consisted of 36 students in class X MP 1 as the experimental class and 36 students in class X MP 2 as the control class. Data were obtained from observations, tests, and student response questionnaires. Data analysis techniques used normality tests, homogeneity tests, N-Gain tests, and hypothesis tests. The hypothesis test results showed a significance value of less than 0,05. Based on these results, it can be concluded that H0 is rejected and HA is accepted, meaning that Gemini has an effect on student learning outcomes